Lung recruitment state during induction of general anaesthesia in a prospective observational clinical study in patients without and with obesity - Silke Borgmann; Kim Linz; Johannes Schmidt; Sara Lozano-Zahonero; Christin Wenzel; Sashko Spassov; Stefan Schumann (Scientific Reports)
Abstract We investigated lung aeration during preoxygenation, mask ventilation, ventilation via endotracheal tube, and the two apnoeic phases in-between. Using electrical impedance tomography we assessed global inhomogeneity, ventral-to-dorsal ventilation distribution, the area of ventilated lung and end-expiratory lung volume loss. Global inhomogeneity was increased after the apnoeic phases (non-obese: 25%, obese: 66%, p<0.005 for both) and re-improved with the first breaths of mechanical ventilation (non-obese) or during mask ventilation only (obese). Ventral ventilation increased after the first (non-obese: 52%, obese: 36%) and second apnoeic phase (non-obese: 46%, obese: 36%) compared to spontaneous breathing (all p<0.005). Ventral ventilation was highest in the first eight breaths following the second apnoeic phase in non-obese patients and in the first breath during mask ventilation in patients with obesity. The area of ventilated lung was smallest during the first or first eight breaths following each apnoeic phase in both patient groups. The decrease of end-expiratory lung volume was more pronounced during the first (non-obese: 411 [95%CI 273, 549] ml, obese: 417 [95%CI 325, 509] ml) compared to the second apnoeic phase (non-obese: 239 [95%CI 166, 312] ml, obese: 285 [95%CI 188, 382] ml, p<0.02 for all cases). We conclude that lung derecruitment occurs during the apnoeic phases of anaesthesia induction and resolves partly with subsequent mechanical ventilation.